Bibliometric analysis on istibdal waqf / Syed Muhammad Asyraf Syed Kamil ... [et al.] - Syed Kamil, Syed Muhammad Asyraf; Abd Mutalib, Hasyeilla; Mohammed Noor, Afiffudin; Hasbulah, Muhamad Husni; Abd Rahman, Nur Athirah (Universiti Teknologi MARA, Perlis, 2024)
Istibdal waqf stands as a powerful tool in tackling underdevelopment issues by enabling the exchange of waqf properties for more beneficial assets. This process significantly contributes to societal welfare through its charitable and religious purposes. As an emerging field, conducting bibliometric studies to examine research trends and patterns related to istibdal waqf is vital. This study analyses worldwide research trends, publication growth, publishing outputs by country, themes of interest, and co-occurrences of author keywords related to istibdal waqf. This study conducted a comprehensive analysis of istibdal waqf using the Scopus database, Microsoft Excel, and VOSviewer 1.6.18. Relevant articles were identified through specific keywords and search strings. Statistical analysis was then applied to the data extracted from the Scopus database. The analysis revealed a steady increase in publishing outputs on istibdal waqf, with most publications originating from Malaysia, Indonesia, and Turkiye. While there was a slight decrease in 2023, the surge in 2022 marked significant growth. Co-occurrence analysis emphasised the strong association between "istibdal" and "waqf," indicating the importance of managing and utilising waqf assets through practices like istibdal. This study provides a comprehensive overview of the research trends in istibdal waqf, highlighting global publications on this emerging topic. The identified co-occurring keywords, such as "cash waqf" and "waqf land," provide a nuanced understanding of istibdal waqf and may be helpful for future scholars investigating under-researched areas. Future scholars can address other themes, such as managing waqf land in general, and expand the scope of research by utilising other databases. The identified trends and patterns can also serve as a reference for policymakers and practitioners engaged in waqf management and Islamic social finance.